Intraoperative cone‐beam CT for head and neck surgery: Feasibility of clinical implementation using a prototype mobile C‐arm1. Issue 7 (12th July 2012) - King, Emma; Daly, Michael J.; Chan, Harley; Bachar, Gideon; Dixon, Benjamin J.; Siewerdsen, Jeffrey H.; Irish, Jonathan C.
Abstract Background Intraoperative 3‐dimensional (3D) imaging in head and neck surgery was developed using a prototype mobile C‐arm for cone‐beam CT (CBCT). This article summarizes its implementation in a prospective pilot and feasibility study. Methods The CBCT C‐arm was used in 12 head and neck surgical oncology cases. Human‐factors engineering methods and expert feedback from surgeons, nurses, and anesthetists were used to evaluate the impact of intraoperative imaging on the surgical environment and clinical workflow. Image quality of CBCT and the perceived clinical utility were evaluated. Results The CBCT C‐arm was successfully incorporated in 12 head and neck cases and streamlined into the surgical environment. Reviewed 3D‐CBCT images were qualitatively sufficient for intraoperative‐guidance for bony detail. Additional artifact management is required to improve soft‐tissue visualization. Conclusions Intraoperative CBCT provides high‐quality images for visualization of bony detail and is feasible during major head and neck surgery with acceptable workflow interruptions. Operations with significant bone ablation and/or reconstruction involving complex 3D anatomical structures are likely to benefit from the updated imaging. © 2012 Wiley Periodicals, Inc. Head Neck, 2013